2017
DOI: 10.3389/fmicb.2017.00561
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Integrons and Phylogenetic Groups among Enteropathogenic Escherichia coli Isolates from Children <5 Years of Age in Delhi, India

Abstract: Integrons by means of horizontal gene transfer carry multidrug resistance genes (MDR) among bacteria, including E. coli. The aim of this study was to determine the antibiotic resistance profiles and the genes associated with them, to gain insights in the distribution of phylogroups, prevalence, and characterization of class 1, 2 and 3 integrons among Enteropathogenic E. coli (EPEC) isolates, from children upto 5 years of age from Delhi and National Capital Region (NCR), India. A total of 120 E. coli isolates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 107 publications
6
14
5
Order By: Relevance
“…In the present study, significant differences in the numbers of isolates with and without integrons were observed ( P < 0.01) between phylogroups D and B1. These agree with those of a previous study that demonstrated that strains associated with phylogroups A and B1 tend to carry integrons more often than those associated with B2 and D [ 10 , 38 ]. In contrast, affiliation with a specific phylogenetic group was not linked to the presence of integrons in E. coli strains recovered from river water [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, significant differences in the numbers of isolates with and without integrons were observed ( P < 0.01) between phylogroups D and B1. These agree with those of a previous study that demonstrated that strains associated with phylogroups A and B1 tend to carry integrons more often than those associated with B2 and D [ 10 , 38 ]. In contrast, affiliation with a specific phylogenetic group was not linked to the presence of integrons in E. coli strains recovered from river water [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…The coding regions of the gene cassettes have no promoters; however, most cassettes encode various antimicrobial resistance genes, with more than 130 distinguishable resistance genes having been found to date [ 6 ]. The majority of class 1 integrons harbors an aminoglycoside adenyltransferase gene ( aadA ) and a dihydrofolate reductase gene ( dfr ), which confer resistance to streptomycin and spectinomycin, and trimethoprim, respectively [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the prevalence of integron genes among E. coli isolates was 57%. This result is in contrast to other study previously published [31], which showed that 80% diarrheagenic E. col isolates carried integron genes. However, other studies showed lower prevalence (22%-43.56%) [8][9][10][11].…”
Section: Discussioncontrasting
confidence: 99%
“…In current study, all E. coli isolates that had integron genes were carried only class 1 integron and none other tested classes. This result is in contrast to other reports previously published, which showed that the class 1 and 2 integrons were detected in E. coli isolates [9,[29][30][31]. However, this result is in agreement with other report previously published, which showed that the class 1 integron was the only type detected among clinical E. coli isolates [8].…”
Section: Discussionsupporting
confidence: 76%
“…A similar study from Iran reported only int1 and int2 genes while none of the DEC strains harbored int3 gene [ 61 ]. Studies from India also reported the presence of int1 and int2 genes in various DEC pathotypes [ 52 , 62 ]. Low prevalence of class 2 integron ( int2 gene) and very rarely class 3 integron ( int 3 genes) have been reported so far among these strains.…”
Section: Discussionmentioning
confidence: 99%